Role of EGFR in the Nervous System - Roberta Romano; Cecilia Bucci (Cells, 2020)
Epidermal growth factor receptor (EGFR) is the first discovered member of the receptor tyrosine kinase superfamily and plays a fundamental role during embryogenesis and in adult tissues, being involved in growth, differentiation, maintenance and repair of various tissues and organs. The role of EGFR in the regulation of tissue development and homeostasis has been thoroughly investigated and it has also been demonstrated that EGFR is a driver of tumorigenesis. In the nervous system, other growth factors, and thus other receptors, are important for growth, differentiation and repair of the tissue, namely neurotrophins and neurotrophins receptors. For this reason, for a long time, the role of EGFR in the nervous system has been underestimated and poorly investigated. However, EGFR is expressed both in the central and peripheral nervous systems and it has been demonstrated to have specific important neurotrophic functions, in particular in the central nervous system. This review discusses the role of EGFR in regulating differentiation and functions of neurons and neuroglia. Furthermore, its involvement in regeneration after injury and in the onset of neurodegenerative diseases is examined.